Augmented Reality for Interactive Path Planning in 3D - Riechmann, Malte; Kirsch, André; König, Matthias (2023 IEEE International Symposium on Mixed and Augmented Reality Adjunct (ISMAR-Adjunct))
In the modern household autonomous service robots are becoming increasingly popular. Changing the behavioral patterns robots working in 3D spaces can propose a challenge for non-expert users. We propose to use augmented reality as an interface to modify the robot’s behavior using virtual artifacts. Our contribution is an AR application that acts as an interface to interactively plan a drone’s path including generating and modifying its path. This also includes two interaction methods for changing the position of virtual objects in 3D space. The first method is based on pan gestures that are commonly in 2D mobile applications, while the second one implements a grasp and release mechanism based on the device’s motion. As a visual aid we employ a simulated drone. A user study was performed to evaluate and compare the two interaction methods. The study had with 18 participants that had to interactively plan a path. The majority of participants preferred the motion-based interaction method, as it was more comfortable to use. However, the touch interaction is more intuitive without any additional information. The resulting paths can be divided in three distinct clusters, which can be used in future work to improve the automatically generated paths.